Induction Chemotherapy for Sinonasal Squamous Cell Carcinoma: A Systematic Review of Kaplan–Meier Individual Patient Data - Ruth S. Goh; Christopher Goh Hood Keng (Journal of Otorhinolaryngology, Hearing and Balance Medicine)
Background/Objectives: This study focuses on examining treatment outcomes of sinonasal squamous cell carcinoma (SNSCC) when induction chemotherapy is added to definitive treatment regimens. A systematic literature search was conducted in the following four bibliographic databases: Embase, MEDLINE, Web of Science and Cochrane Central Register of Controlled Trials (CENTRAL). A total of 604 patients across 12 studies were included in the final review. Methods: This systematic review adheres to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Pooled survival curves were derived from reconstructed individual patient data using Guyot et al.’s methodology, in which K-M curve drops are measured relative to the numbers-at-risk and number of events. Results: In this study, 71% of patients were male and 93% presented with late-stage (T3–4) cancer. The 24-month and 60-month overall survival rates were 55.1% and 35.0%, respectively. The 24-month disease-free survival was 44.4% and remained relatively stable at 42.1% at 60 months. The local control rate remained stable from 24 to 60 months at 72.7%. Conclusions: Compared to the results from the existing literature, this review reveals an overall survival and disease-free survival (DFS) that is comparable to that of other multimodality treatment options. The local control rate (LCR) was also high. This review suggests that induction chemotherapy can be utilised for patients with advanced SNSCC.